Penerapan Metode Reward Pada Pembelajaran Bahasa Arab Berbasis Online Learning - Khairil Anwar (An Naba, 2023)
This research is motivated by a lack of teacher creativity in online teaching and learning activities, teachers often find it difficult when carrying out the learning process carried out in online-based learning applications due to lack of strategy and activeness of students during the learning process. With the online reward method for students in the learning process is a step to solve problems that exist in online learning today, especially in Arabic subjects. This research was conducted to see how much influence the Reward method has in online learning-based Arabic learning. The place of this research is at MTs Darul Huffaz Pesawaran. In this study, researchers used a quasi-experimental approach that tested the independent and dependent variables. As for the sampling technique, the researcher used a purposive sampling technique with 22 students in the experimental class (VIII-G) and 22 students in the control class (VIII-I). The data collection technique used is a test. The results of this study indicate that there is an effect of the application of the reward method on students' Arabic learning outcomes, as evidenced by the results of the Independent Samples Test with a sig. (2-tailed) namely 0.000 <0.05.